Intraocular lens power calculation after intrastromal femtosecond laser treatment for presbyopia: theoretic approach - Rabsilber, Tanja Marina; Haigis, Wolfgang; Auffarth, Gerd U.; Mannsfeld, Annett; Ehmer, Angela; Holzer, Mike P. (Journal of cataract and refractive surgery, 2011)
PURPOSE: - To evaluate the accuracy of intraocular lens (IOL) power calculation after an intrastromal femtosecond laser procedure to treat presbyopia using a theoretic approach. - SETTING: - International Vision Correction Research Centre, Department of Ophthalmology, University of Heidelberg, Heidelberg, Germany. - DESIGN: - Nonrandomized clinical trial. - METHODS: - Preoperatively and 12 months after intrastromal femtosecond laser treatment (IntraCor) of presbyopia, biometry was performed by partial coherence interferometry (PCI) (IOLMaster). The postoperative keratometry (K) values and IOL power calculation formulas (Holladay I, Haigis, SRK/T, Hoffer Q) were compared with results derived from the clinical history method, taking the manifest refraction change into account. - RESULTS: - The study enrolled 25 patients (median age 54 years). Three eyes were excluded for age-related lens changes. The median spherical equivalent change in the other 22 eyes was −0.38 diopter (D). The median difference in K values between the clinical history method and PCI was −0.21 D, resulting in a median IOL power difference between −0.23 D (SRK/T) and −0.29 D (Haigis) (range −1.58 to +1.00 D). The IOL power was underestimated in 59.1% of cases with the Hoffer Q and 63.6% of cases with the Holladay I, Haigis, and SRK/T. There was a difference of ±0.75 D in 72.7% of eyes using the Holladay I, Haigis, and Hoffer Q and in 86.4% of eyes using the SRK/T. Neither K values nor IOL power differences were statistically significant (P > .17). - CONCLUSION: - Intraocular lens power calculation using modern standard formulas incorporated in a PCI biometry device after intrastromal femtosecond presbyopia treatment was reliable, with minimum underestimation on average.
Gesehen am 08.09.2022